Epitaxy Enhancement of Piezoelectric Properties in P(VDF‐TrFE) Copolymer Films and Applications in Sensing and Energy Harvesting. (13th September 2020) - Yang, Jiang; Chen, Qiusong; Xu, Fan; Jiang, Hanxiao; Liu, Weilin; Zhang, Xiaoqing; Jiang, Zaixiu; Zhu, Guodong
Abstract: With the rapid development of wearable and flexible electronics, energy harvesting from the environment has attracted much attention. As one representative piezoelectric polymer, poly(vinylidene fluoride‐trifluoroethylene) [P(VDF‐TrFE)] is an expected candidate for mechanical energy harvesting and self‐powered mechanical sensors due to its flexibility and moderate piezoelectricity. However, low crystallinity and electroactivity limit its electric performance. Controllable modulation of microstructure and crystallization is one feasible measure to enhance piezoelectric property. Here the piezoelectric properties of epitaxial P(VDF‐TrFE) films which are fabricated via removable polytetrafluoroethylene template method are reported. Piezoelectric measurement between 50 and 800 Hz presents an averaged d 33 coefficient of −40.7 pC N −1 for epitaxial film, ≈61% enhancement to that of non‐epitaxial one. Transverse piezoelectric experiment indicated that epitaxy process enhanced open‐circuit voltage and short‐circuit current outputs. Simple piezoelectric energy harvesters are prepared by depositing both epitaxial and nonepitaxial films on flexible polyimide substrates. Epitaxial film shows a maximum generated power density of 0.118 µW cm −2 and energy conversion efficiency of 0.81%, both of which are much larger than those from nonepitaxial film (0.047 µW cm −2 and 0.30%). Piezoelectric films are used to monitor bending, punching, twisting and finger tapping operations, where epitaxial film exhibited larger open‐circuit voltage responses than nonepitaxial one. Abstract : Enhancement of piezoelectric properties in copolymer films is realized via removable polytetrafluoroethylene (PTFE) template method. Epitaxy process induces an increase of d 33 coefficient by ≈61%. Transverse piezoelectric experiments indicate that epitaxy process greatly enhances open‐circuit voltage and short‐circuit current outputs. Applications of epitaxial copolymer films in sensing and energy harvesting are also illuminated.